HUBUNGAN PERSEPSI TENTANG PELATIH DAN MOTIVASI LATIHAN SISWA DALAM EKSTRAKURIKULER BOLA BASKET - Ani Kurniawati; Ribut Wahidi (Journal of Physical Education and Sport Science, 2020)
This study aimed to determine the significant relationship between perceptions of trainer and student's training motivation in women's basketball extracurricular activities at SMPN 1 Singaparna. The method that is used is descriptive with correlational techniques. The population and sample of the study were 20 students who participated in extracurricular basketball activities at SMPN 1 Singaparna. The instrument is used a questionnaire or it is also called a questionnaire taken from Arikunto (2002). Processing and data analysis in research using statistical methods. The results of data processing and data analysis for each component of the questionnaire distribution of students' perceptions from the trainer's task component had an actual score of 78.00% with 10 statement items, the trainer's personality component had an actual score of 78.25% with 8 statement items. The students' training motivation from the external motivation component had an actual score of 79.24% with 17 items. The intrinsic motivation component had an actual score of 80.32% with 19 statement items. The conclusion of this study can be concluded that the perception of the trainer had a significant relationship with students' training motivation in extracurricular activities for women's basketball at SMPN 1 Singaparna.